Wide-Gap p-μc-Si1-xOx:H Films and Their Application to Amorphous Silicon Solar Cells - Taweewat Krajangsang; Sorapong Inthisang; Aswin Hongsingthong; Amornrat Limmanee; Jaran Sritharathikhun; Kobsak Sriprapha (International Journal of Photoenergy)
Optimization of p-type hydrogenated microcrystalline silicon oxide thin films (p-μc-Si1-xOx:H) by very high frequency plasma enhanced chemical vapor deposition 40 MHz method for use as a p-layer of a-Si:H solar cells was performed. The properties of p-μc-Si1-xOx:H films were characterized by conductivity, Raman scattering spectroscopy, and spectroscopic ellipsometry. The wide optical band gap p-μc-Si1-xOx:H films were optimized by CO2/SiH4 ratio and H2/SiH4 dilution. Besides, the effects of wide-gap p-μc-Si1-xOx:H layer on the performance of a-Si:H solar cells with various optical band gaps of p-layer were also investigated. Furthermore, improvements of open circuit voltage, short circuit current, and performance of the solar cells by using the effective wide-gap p-μc-Si1-xOx:H were observed in this study. These results indicate that wide-gap p-μc-Si1-xOx:H is promising to use as window layer in a-Si:H solar cells.